Hidden Depths: A Unique Biodiversity Oasis in the Persian Gulf in Need of Further Exploration and Conservation - Samimi-Namin, Kaveh; Hoeksema, Bert W. (Diversity (Basel), 2023)
The Persian Gulf, a young and shallow epicontinental sea, is known for its unique geological and oceanographic characteristics that foster its diverse and productive marine ecosystems. A substantial portion of the Gulf’s seafloor consists of unconsolidated soft sediments, making it unsuitable for colonization by many sessile organisms. Consequently, relatively few hard grounds and submerged banks provide suitable habitats for benthic and substrate dwellers. This study documents a unique marine habitat on an offshore submerged bank, likely a raised salt dome, south of Qeshm Island, Iran. This area is home to a high concentration of ahermatypic coral species and remains relatively sheltered from human activities. The bank’s geographic location allows inflow currents from the Strait of Hormuz to transport larvae and nutrients, providing suitable substrates for various sessile invertebrates. Moreover, it causes the formation of Taylor columns, which affect fluid dynamics and circulation patterns, indirectly enhancing biodiversity. Despite facing risks from large-scale regional and localized threats, the bank’s remoteness from the main coast and its depth provide some protection. This study emphasizes the need for continued exploration and the implementation of effective conservation measures in the region, along with additional research to clarify the ecological and physical parameters supporting its diversity. It also presents the first in situ photographic evidence for the occurrence of some octocoral genera in the Gulf. Future research should investigate how the species compositions of hidden banks and shoals contribute to the overall biodiversity of the Persian Gulf.